Organizational Commitment on Member Performance Through Job Satisfaction - Putri, Jihan Febriyanti Asmara; Yendra, Yendra; Marihi, La Ode (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aims to examine the effect of Organizational Commitment on Member Performance with Job Satisfaction as a mediating variable in the Gegana Detachment of Sat Brimob Polda Papua. Research Design and Methodology: Quantitative methods were employed in this study, utilizing Structural Equation Modeling (SEM) for data analysis. Data were collected through a questionnaire administered to members of the Gegana Detachment. Findings and Discussion: The results demonstrate that Organizational Commitment significantly influences Member Performance, both directly and through Job Satisfaction as a mediating factor. Organizational Commitment positively impacts Job Satisfaction, subsequently enhancing Member Performance. This underscores the positive relationship among these variables, indicating that high organizational commitment leads to greater job satisfaction, thus enhancing performance. Implications: This research contributes to the field of human resource management, particularly in policing contexts. It underscores the significance of Organizational Commitment and Job Satisfaction in enhancing Member Performance. The study offers empirical evidence for policymaking in police human resource management, emphasizing the importance of fostering commitment and job satisfaction for optimal performance. However, limitations include a sample restricted to a single police unit and a cross-sectional design, which does not capture the temporal dynamics of the variables. Future research should employ a broader sample and a longitudinal design, while also considering additional variables, such as leadership style and organizational culture, to provide more comprehensive insights.